The level of awareness among Bumiputera towards the existence of life insurance Takaful / Ira Amiera Zulkefli - Zulkefli, Ira Amiera (Facuty of Business and Management, 2010)
This research is about the level of awareness among bumiputera towards the existence of Life Insurance Takaful. The independent variable such as expand product portfolio, increase market visibility, increase synergy and improve efficiency, are being identify in order to make an investigated whether or not these independent variable have significant and influenced the performance of employees. This research was conducted in Nilai’s area where 50 questionnaires were distributed and 50 questionnaires were returned. To obtain data, researcher was used two methods that are primary and secondary data. Data analyzed using reliability test, Pearson correlation analysis, and frequency analysis. Based on the analysis, the results from correlation have shown three of the variables which are expand product portfolio, increase market visibility and improve efficiency has no significant relationship and another one independent variable which is increase synergy has a significant relationship.